PENGARUH KEMACETAN DI SIMPANG CILIWUNG TERHADAP DERAJAD PELAYANAN DI SIMPANG PROGRESIF - Dwi Ratnaningsih, Rudy Ariyanto, Supiyono, (Prokons: Jurnal Teknik Sipil, 2017)
Abstract Highway in Malang there that needs to be analyzed is Intersections Letjend S. Parman Street ? Ciliwung Street and Letjend Sutoyo Street ? Letjend Selorejo. The road is an arterial road in the city of Malang with a high vehicle density level (Saputra, 2013). The Street was a high traffic flow led to queues or long saturated flow that is not supported by the settings of the light signals in accordance with the conditions in the field so often causes congestion. From finding a solution the traffic density in the study Letjend S Parman Street ? Ciliwung Street and Letjend Sutoyo Street ? Letjend Selorejo with Indonesia Highway Capasity Manual (IHCM). After stages 3-signal coordination calculation in Ciliwung Intersection of Malang, Intersection obtained time peak hours at the intersection area occurred at 11.00 ? 12.00 GMT. Performance 3-waay junction on the Ciliwung Malang at this time has not met the target. Seen from there is still a Degree of Saturation (DS) which do not meet the targets ( ? 0,75), namely 0,83. After having don e engineering into 3 phases and cycle time 100 minutes Degree of Saturation (DS) be 0,77. Keywords: intersection, peak hours, capacity and degree saturation